TERRITORIAL ORGANIZATION OF SOCIAL SECTORS IN THE KHOREZM REGION - Atayeva Nazira Polvonnazirovna; Shomurodov Mansurbek Jonibek ugli (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Abstract: This article analyzes the current state and development prospects of the social sector in the Khorezm region. To assess the effectiveness of ongoing reforms in education, healthcare, employment, social protection, and housing construction in the Khorezm region, research methods such as economic and geographical analysis, mathematical and statistical analysis, and mathematical modeling are used. Recommendations for modernizing social infrastructure, improving living standards, and enhancing the quality of social services are also proposed.